Scalar based Common Mode Voltage Reduction PWM Techniques for Dual Inverter Fed Open End Winding Five-Phase Induction Motor Drives - Balakrishna, J.; Bramhananda Reddy, T.; Vijay Kumar, M. (International Journal of Engineering and Technology, 2018)
This paper presents a simplified approach for common mode voltage (CMV) reduction for the dual inverter fed open end winding five-phase induction motor drives. This paper presents the simplified PWM techniques for three-level and four-level topologies of open end winding five-phase induction motor drive. In this method reference voltage signals are synthesized by injecting the zero sequence signals. Through these proposed methods, a reduction of 66.6% in three-level topology and 40% in four-level topology is observed in peak to peak voltage of common mode voltage when compared to conventional space vector PWM technique. Number of levels in common mode voltage is reduced from 5 levels to 2 levels in three-level topology and 6 levels to 3 levels in four-level topology when compared to a conventional space vector PWM technique. Simulation studies are performed to validate the proposed simplified methods.